A Project Feasibility Study on Bislig Coal-Fired Thermal Power Plant - Doctora, Gerard T.; Manalo, Marla U.; Pobre, Nancy T.; Santiago, Nelson (Diliman, Quezon City College of Engineering, 1986)
The proposed Bislig coal-fired thermal power plant is a 2x100 MW power station to be located in Barangay Lawigan, Bislig, Surigao del Sur. It is in the eastern cape side of the Bislig Bay about seven kilometers from the Mangagot wharf. The power plant will be connected with the Mindanao power grid. The present grid is served principally by hydro-electric and diesel plants. If ever, the Bislig power station will be the first coal-fired thermal power plant in the Mindanao region. The project is aimed to supply the equipment of the power expansion program in Mindanao. It will also support the government?s program towards self-reliance in energy through a gradual shift to non-oil energy sources. It will utilize coal which is available locally. The major users of electricity in Mindanao are the industries, private utilities and the cooperatives. The Mindanao power grid is the main source of power for the whole Mindanao region. Eleven major industrial projects were lined up by the Philippine government through the Ministry of Trade and Industry for implementation, to accelerate the industrial development program. The anticipated increase of power requirement in this region makes up the demand of electricity for the grid. The Mindanao power grid which is under the National Power Corporation is a monopoly in the large scale production of electric power. Competition only exists in the smaller scale power distribution like cooperatives. Fig. 3.1 and Fig 3.2 show the increasing total installed capacity in MW and system energy in GWH, respectively, of the generating plants of NAPOCOR. These make up the supply needed in order to meet the increasing demands of electric power in the region. Figure 4.1 shows the graphs of the system peak demand and total installed capacity in MW. The graph shows how the Bislig coal thermal power plant is needed in order to satisfy the increasing demand of electricity during 1992 and 1993. In Fig 4.2, the system energy requirement in GWH from 1991 onwards is higher than the system energy supply in GWH for the same years. This is due to the energy losses incurred along the way in the transmission of the electric power from the generating stations to the consumer. The selling price or charges of electric power is shown in Table 5.1. These price charges are of 1986 values. The fluctuation of charges over time, specifically during 1992 and 1993 is mainly based on the price of fuel and on the economic conditions of the country. Anyhow, electric power is a basic necessity and since NAPOCOR supplies power on a large scale, demand would not be greatly affected by increases in charges. From above, it can be concluded that the Bislig coal-fired thermal power plant project is marketably viable.
Feasibility Study
Typescript
Submitted in partial fulfillment of the course requirements in IE 153 : Project Development and Management
Keywords: Coal-fired power plants--Philippines.; Electric power production; Participatory monitoring and evaluation (Project management)